Quality in Web Translation: An Investigation into UK and Italian Tourism Web Sites - Patrizia Pierini (JoSTrans: The Journal of Specialised Translation)
This paper sets out to investigate quality in the translation of tourist discourse on the Web. It is divided into two parts. The first discusses theoretical issues: localisation and translation; which theoretical framework for Web translation; the criteria to assess translation quality. The second part is an investigation into a corpus of UK and Italian tourism Web sites: the criteria outlined are employed to explore transfer strategies, and translation problems and errors. The focus is on the tourist language regarding accommodation; the data considered are taken from the accommodation page of tourist board sites, and hotel sites.